2013
DOI: 10.1097/nmd.0b013e3182848ae0
|View full text |Cite
|
Sign up to set email alerts
|

Object Relations, Reality Testing, and Social Withdrawal in Schizophrenia and Bipolar Disorder

Abstract: In this study, we investigated the relationships between observed social withdrawal (Positive and Negative Syndrome Scale [PANSS] Passive Social Withdrawal and PANSS Active Social Avoidance), subjectively experienced social withdrawal (Social Functioning Scale [SFS] Withdrawal and SFS Interpersonal Behavior), and their associations to the underlying psychological patterns of Object Relations and Reality Testing. Patients with schizophrenia (n = 55) and bipolar disorder (n = 51) from the ongoing Thematically Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For this reason, they probably less often had florid positive symptoms or primary disorder-induced anxiety symptoms to report [9]. Third, avoidance behavior may be less prominent in SSA patients due to their common withdrawal from social roles, and hence, less frequent exposure to common anxiety-provoking situations [54–56]. Furthermore, these patients often experience negative symptoms, rendering some of them emotionally numb and indifferent to situations that tend to cause anxiety in other populations [57].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, they probably less often had florid positive symptoms or primary disorder-induced anxiety symptoms to report [9]. Third, avoidance behavior may be less prominent in SSA patients due to their common withdrawal from social roles, and hence, less frequent exposure to common anxiety-provoking situations [54–56]. Furthermore, these patients often experience negative symptoms, rendering some of them emotionally numb and indifferent to situations that tend to cause anxiety in other populations [57].…”
Section: Discussionmentioning
confidence: 99%
“…To assess social impairment we used two items from the PANSS: 1) active social avoidance defined as diminished social involvement associated with unwarranted fear, hostility or distrust; and 2) passive social withdrawal defined as diminished interest and initiative in social interactions. Whether these two items represent distinct or shared constructs remains unclear as some studies find they are distinct (Hansen et al, 2013) and others show they load on a common factor (Van den Oord et al, 2006). In our sample the two items were modestly correlated (r = .48, p = .02), therefore we analyzed them separately.…”
Section: Methodsmentioning
confidence: 99%
“…As with the SCORS, past studies have shown that all subscales should have pointed to the difference. This could be explained by the use of the BORRTI mostly in clinical settings, as in the SCORS case (e.g., Hansen, Torgalsbøen, Rossberg, Andreassen, Bell & Melle, 2012;Hansen, Torgalsbøen, Røssberg, Romm, Andreassen, Bell & Melle, 2013;Huprich, Pouliot & Bruner, 2012). The fact that only the AL subscale exhibited significant differences could also be explained by the fact that AL contains high loadings on the greatest number of BORRTI items and appears to represent the broadest dimension of OR measured (Bell, 1995;Bell et al, 1986).…”
Section: Discussionmentioning
confidence: 99%